Space in television historical fiction: the nation seen through the past in Gritos de muerte y libertad - Charlois Allende, Adrien José (Universidad de Chile. Instituto de la Comunicación e Imagen, 2018)
This work proposes to analyze and describe three particular forms of construction of the national space in the Mexican historical miniseries Gritos de muerte y libertad. Under the pretext of commemorating 200 years of Mexican independence in 2010, Televisa opted to build a narrative about the national heroes who participated in the War of Independence. On this historiographical perspective on the birth of the nation, the production revealed ways of articulating the person within time and space. Visual and auditory resources allowed assembling a cartography of the natio- nal, as well as different metaphors in which the historical moment is linked with the space of its representation. Understanding space as a narrative construction, the work describes three spatial forms in the miniseries: the space of the national, the private space as a reflection of the nation and space as a scenario of heroism